2019
DOI: 10.1016/j.jid.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B1a Cells Suppress Melanoma Tumor Immunity via IL-10 Production and Inhibiting T Helper Type 1 Cytokine Production in Tumor-Infiltrating CD8+ T Cells

Abstract: In tumor immunity, the participation of IL-10eproducing regulatory B cells (Bregs), which play an important role in suppressing immune responses, is unclear. In this study, we demonstrated an increase in B16F10 melanoma growth and a decrease in the proportion of IFN-ge and TNF-aesecreting tumor-infiltrating CD8 þ T cells in B cellespecific PTEN-deficient mice in which Bregs were expanded. The number of tumor-infiltrating Bregs significantly increased in B cellespecific PTEN-deficient mice. More than 50% of tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
(54 reference statements)
2
39
0
Order By: Relevance
“…B cells are divided into two opposing B‐cell subsets, namely regulatory B cells and effector B cells . Regulatory B cells negatively regulate immune responses by the production of anti‐inflammatory cytokines, such as interleukin (IL)‐10 . Regulatory B cells have been found to be decreased and/or functionally impaired in various autoimmune diseases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B cells are divided into two opposing B‐cell subsets, namely regulatory B cells and effector B cells . Regulatory B cells negatively regulate immune responses by the production of anti‐inflammatory cytokines, such as interleukin (IL)‐10 . Regulatory B cells have been found to be decreased and/or functionally impaired in various autoimmune diseases .…”
Section: Discussionmentioning
confidence: 99%
“…18 Regulatory B cells negatively regulate immune responses by the production of anti-inflammatory cytokines, such as interleukin (IL)-10. 19,20 Regulatory B cells have been found to be decreased and/or functionally impaired in various autoimmune diseases. [21][22][23] cytokines, such as IL-6.…”
Section: Serum Baff Levels (Ng/ml)mentioning
confidence: 99%
“…IL-10 inhibitors are a known negative regulator of autoimmunity and inflammation (Bouaziz et al, 2008;Iwata et al, 2011;Matsushita et al, 2008). Kobayashi et al (2019) showed that in Bregs where PTEN was inactivated, there was a significant increase in B16F10 volume and decreased survival in PTEN-deficient mice injected subcutaneously with B16F10 melanoma cells compared with control mice (Kobayashi et al, 2019). See Figure 1 from Kobayashi et al (2019).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%
“…2. What likely effect would increased PTEN have on B16F10 melanoma volume and mortality as described in Kobayashi et al (2019)?…”
mentioning
confidence: 99%
See 1 more Smart Citation